Trust as a Social Capital for Entrepreneurship to Create Innovation - Andrean Kisima Oei; Aluisius Hery Pratono (Institut Teknologi Sepuluh Nopember, 2020)
One indicator of the success of an entrepreneur can be measured by the innovation he created. It is essential that an entrepreneur has the ability to interact and work together in groups so that innovation can be created. Trust is a social capital that makes internal cooperation work well. Competitive aggressiveness is one of the dimensions of entrepreneurial orientation that is still contractual in its impact on innovation. This study wants to find out the relationship between trust in competitive aggressiveness and innovation and the effect of competitive aggressiveness on innovation. Data collection collected using a questionnaire consisting of two parts, the first in the form of open questions to find out problems or difficulties experienced by students and in the second part in the form of questions with a Likert scale. The data took from students who took entrepreneurship courses at UBAYA university. The data collected amounted to 100 and then processed by PLS-SEM analysis using α = 5%. This study found that trust is a critical factor for innovation creation and positively influences to bring about competitive aggressiveness. Trusts make the process of working together and sharing information in groups work well. Other findings from this study also show that competitive aggressiveness has a positive impact on innovation.